2018
DOI: 10.1186/s12884-018-1900-4
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in healthy term newborns is related to delivery mode: a prospective observational study

Abstract: BackgroundEarly postnatal period is characterized by dramatic adaptation changes of cardiovascular and respiratory systems in newborns. There is still insufficient data regarding maturation of autonomic regulatory mechanisms in neonates early after delivery. Aim of this study was to analyze cardiac autonomic regulation in newborns within the first few postnatal days in relation to different modes of delivery using time and spectral heart rate variability analysis.MethodsEutrophic healthy term newborns (n = 46)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
0
22
1
4
Order By: Relevance
“…Previous authors have found differences in HRV values across different delivery modes. Kozar et al (2018) reported lower HFn and higher LFn in babies born via cesarean section than in babies born vaginally. It is possible that their finding is related with the use of Thiopental for general anesthesia (GA) in all their elective sections (Riznyk et al, 2005; Tsuchiya et al, 2006) rather than with the delivery mode, whereas in our study there was no use of any GA. Our interpretation is that HRV will indicate a difference between delivery modes if there is a difference in wellbeing, therefore, in our study, this would have been associated with the use of instruments during delivery due to difficult extraction.…”
Section: Discussionmentioning
confidence: 91%
“…Previous authors have found differences in HRV values across different delivery modes. Kozar et al (2018) reported lower HFn and higher LFn in babies born via cesarean section than in babies born vaginally. It is possible that their finding is related with the use of Thiopental for general anesthesia (GA) in all their elective sections (Riznyk et al, 2005; Tsuchiya et al, 2006) rather than with the delivery mode, whereas in our study there was no use of any GA. Our interpretation is that HRV will indicate a difference between delivery modes if there is a difference in wellbeing, therefore, in our study, this would have been associated with the use of instruments during delivery due to difficult extraction.…”
Section: Discussionmentioning
confidence: 91%
“…Підсумовуючи отримані результати варто зазначити, що стан здоров'я вагітної жінки, перебіг вагітності та пологів, термін гестації мають відомий впив на розвиток гіпоксичних подій у новонароджених та формування порушень адаптаційних процесів при народженні [7,8,9]. Отримані нами дані свідчать про розповсюдженість порушень серцевосудинної, ендокринної та сечовивідної систем у матерів обстежених новонароджених, що може бути корисним для формування груп ризику щодо народження дітей з гіпоксією.…”
Section: особливості перинатального анамнезу та стан вегетативної регunclassified
“…Одержані дані щодо результатів аналізу ВСР узгоджуються з дослідженнями фахівців щодо негативного впливу гіпоксії на процеси регуляції серцевого ритму у новонароджених [6,7]. В умовах проведеного дослідження доведено зниження всіх параметрів ВСР у новонароджених як з гіпоксією при народженні, так і в групах передчасно народжених немовлят, з найнижчими показниками саме в групі передчасно народжених з гіпоксією.…”
Section: особливості перинатального анамнезу та стан вегетативної регunclassified
“…На сьогодні тривають пошуки нових методик і показань для проведення аналізу варіабельності серцевого ритму (ВСР). Літературні дані свідчать про вивчення ВСР з метою характеристики вегетативної регуляції, діагностики порушень ритму серця у новонароджених з різним терміном гестації та вагою [1,2] та визначення ризику розвитку раптової малюкової смертності [3]; для оцінки впливу особливостей пологової діяльності [4], інфекційного процесу [5,6] на автономну регуляцію та визначення стану дитини при народженні [7]. Залишаються актуальними питання пошукузалежності змін ВСР від характеру постгіпоксичного ураження ЦНС [8], впливу лікувальної гіпотермії [9] тапрогнозування ступеня неврологічного ураження або несприятливого неврологічного розвитку у новонароджених з неонатальною енцефалопатією [10].…”
Section: вступunclassified
“…Отримані дані свідчать про більшу активність симпатичного ланцюгу вегетативної регуляції серцевого ритму у дітей, які перенесли гіпоксію, що узгоджується з даними літератури [4,10]. Цей механізм можна пояснити адаптаційною відповіддю організму на синтез та викид стресових фізіологічно активних речовин [29].…”
Section: результати дослідження та їх обговоренняunclassified